A criação em Nietzsche: por uma estético-ética da criatividade - Apolinário, José Antônio Feitosa (2011)
This research aims at investigating the possibilities of conceiving an aesthetic based ethics from the notion of creation within a nietzschean context. Such notion is clearly revisited and operated by the philosopher, along with the main figures of thought developed in his reflections, which is an important element for the understanding of human existence. From such standpoint, we conjecture to be possible a reconfiguration of the ethos based in the nietzschean sense of creation, of the creating (schaffen) as construction of values according with the cosmic-physiological activity (in accordance with the belated image of the will to power) and of the experimentation in frank correspondence with the opening of the tragic world, artistically affirmed as an existential aesthetic. Along the development of this hypothesis, the use of the expression creativity was chosen, with which it is believed to achieve a kind of creative human, as a concretization of this aesthetic-ethics, designated by the image of a human, scarce human . Such being, according to our understanding, would not be the man of resentment bound to metaphysics and morality, nor would it be the beyond-man (Übermensch), as outstripping experience or proposal to tackle with the whole vacuum of the meaning of life: the human, scarce human is right between the resentful man and the superhuman. It is argued that this rare creative man, as scarce human, can be found in some typological figures outlined by Nietzsche in his philosophical journey. By using a critic-analytical approach of nietzschean texts, along with extensive hermeneutical analyses, a diachronic identification of ideas, arguments and assertions that consolidate the referred hypothesis is sought to be achieved. The structure of this research is divided in four chapters. In the first, the notion of creation is analyzed in its nietzschean kernel conception, emphasizing its constant and fundamental emerging along with the conceptions developed by latter Nietzsche. In the second, the nietzschean arguments that discuss the creational activity, the concept of experience, the tragic knowledge and the imperative of life-affirming, as formational criteria of an alternative ethos to traditional ethics, are investigated. In the third, some of the issues left by interpreters that have dealt with the dimension assumed by art in Nietzsche s Philosophy are examined; comprising reasoning to stand behind the argument that creation is taken as quality of the will to power in its process of concretization, in a sense of artistic creation. In the last chapter, we investigate the Nietzschean indications of a possible human greatness connected to an active and creative typology, by analyzing of the type lord, aristocratic and noble as well as others figures constructed by the philosopher. In addition, the insertion of Nietzsche s reflections in the field of philosophical anthropology is questioned, pondering on the articulation between human condition and evaluation, which is a characteristic of his mature constructs. After such survey, the possibilities of this kind of human, taken here as creative, are discussed as such being creates values by expression of power as a simultaneously affirmative activity.